O uso da Web 2.0 na educação: um estudo de caso com professores participantes do projeto um computador por aluno (UCA) - Pontes, Renata Lopes Jaguaribe (2011)
This research analyzes how occurs the appropriation and educational use of Web 2.0 for teachers participating in the project One Laptop per Student (UCA) of a municipal school in Fortaleza, Ceará. The methodological approach adopted was qualitative and the strategy employed was the case study with three elementary school teachers. Data were collected through participant observation and semi-structured interview techniques. The results indicate that the teachers did not know the pedagogical possibilities of Web 2.0, but during the investigation had positive changes in teaching and instrumental use of the tools, as well conducted experimental classes in which students are encouraged to interact and collaborate on network. Within this context, the UCA project was shown as an excellent opportunity to encourage innovative educational practices through the philosophy of Web 2.0. However, for these advances continue teachers need more time to appropriate and plan lessons with the tools of Web 2.0.